(untitled) (Research, Society and Development, 2021)
This was aimed to evaluate the effects of plant arrangements and cutting systems on the yield and quality of dual purpose wheat. The present study was conducted in the years 2015, 2016 and 2017 in Frederico Westphalen, belonging to the state of Rio Grande do Sul. The dual purpose wheat genotype used was BRS Tarumã. For this, five sowing densities were used, namely: 75, 150, 225, 300 and 375 seeds per square meter. The analysis of variance revealed significance for the interaction sowing density x cutting systems x chemical quality for the variables dry matter per hectare, lipids, digestible fiber in acid detergent, lignin, cellulose, mineral matter, total carbohydrates and non-fibrous carbohydrates. The positive effects on yield and bromatological quality of the forage are obtained by arranging plants and cutting systems through the sowing density of 300 to 375 seeds per meter with the practice of up to two cuts in dual purpose wheat. Superior dry matter per unit area was observed in the second cut, which was defined by the stimulation of tillering, regrowth and split nitrogen fertilization. Since, the superior bromatological quality is determined by the magnitude of non-fibrous carbohydrates in the forage.